The coordination complex formed by oxalic acid and chromate and the mechanism for enhanced photoreduction of Cr(Ⅵ) under visible-light irradiation - GUAN Yingying; WANG Hao; GE Xiaoming; DENG Likai; DENG Bin; MU Yi*; ZOU Jianping* (能源环境保护)
Oxalic acid, which mainly originates from root exudation and plant residue decomposition, is one of the most widely existiug carboxylic acids, and has a dramatic impact on the reduction of chromate in natural waters. In this study, isothermal titration calorimetry (ITC), theoretical calculations, and electrospray ionization high resolution mass spectrometry (ESI-HRMS) analysis revealed that oxalic acid could complex with chromate to form a Cr(Ⅵ)-oxalate complex via an esterification process at pH≤4. The in situ generated HC2CrO7 complex was a visible-light-active species, and visible light could induce electron transfer from the oxalate unit to the Cr(Ⅵ) within the HC2CrO7 complex via a HOMO-LUMO electronic transition, resulting in Cr(Ⅵ) reduction. Subsequently, we verified the Cr(Ⅵ) reduction intermediates, and the hypotoxic Cr(Ⅲ) species [Cr3+-(C2O2-4)3] 3- was the final product. Finally, the pathway of Cr(Ⅵ) reduction by oxalic acid under visible-light irradiation was proposed. This study will provide a theoretical basis for efficient photoreduction of Cr(Ⅵ) pollution using oxalic acid.